If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -1) = 2x(2x) + 5x + -12 Reorder the terms: x(-1 + 2x) = 2x(2x) + 5x + -12 (-1 * x + 2x * x) = 2x(2x) + 5x + -12 (-1x + 2x2) = 2x(2x) + 5x + -12 Remove parenthesis around (2x) -1x + 2x2 = 2x * 2x + 5x + -12 Reorder the terms for easier multiplication: -1x + 2x2 = 2 * 2x * x + 5x + -12 Multiply 2 * 2 -1x + 2x2 = 4x * x + 5x + -12 Multiply x * x -1x + 2x2 = 4x2 + 5x + -12 Reorder the terms: -1x + 2x2 = -12 + 5x + 4x2 Solving -1x + 2x2 = -12 + 5x + 4x2 Solving for variable 'x'. Reorder the terms: 12 + -1x + -5x + 2x2 + -4x2 = -12 + 5x + 4x2 + 12 + -5x + -4x2 Combine like terms: -1x + -5x = -6x 12 + -6x + 2x2 + -4x2 = -12 + 5x + 4x2 + 12 + -5x + -4x2 Combine like terms: 2x2 + -4x2 = -2x2 12 + -6x + -2x2 = -12 + 5x + 4x2 + 12 + -5x + -4x2 Reorder the terms: 12 + -6x + -2x2 = -12 + 12 + 5x + -5x + 4x2 + -4x2 Combine like terms: -12 + 12 = 0 12 + -6x + -2x2 = 0 + 5x + -5x + 4x2 + -4x2 12 + -6x + -2x2 = 5x + -5x + 4x2 + -4x2 Combine like terms: 5x + -5x = 0 12 + -6x + -2x2 = 0 + 4x2 + -4x2 12 + -6x + -2x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 12 + -6x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(6 + -3x + -1x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(6 + -3x + -1x2)' equal to zero and attempt to solve: Simplifying 6 + -3x + -1x2 = 0 Solving 6 + -3x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -6 + 3x + x2 = 0 Move the constant term to the right: Add '6' to each side of the equation. -6 + 3x + 6 + x2 = 0 + 6 Reorder the terms: -6 + 6 + 3x + x2 = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 3x + x2 = 0 + 6 3x + x2 = 0 + 6 Combine like terms: 0 + 6 = 6 3x + x2 = 6 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 6 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 6 + 2.25 Combine like terms: 6 + 2.25 = 8.25 2.25 + 3x + x2 = 8.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 8.25 Calculate the square root of the right side: 2.872281323 Break this problem into two subproblems by setting (x + 1.5) equal to 2.872281323 and -2.872281323.Subproblem 1
x + 1.5 = 2.872281323 Simplifying x + 1.5 = 2.872281323 Reorder the terms: 1.5 + x = 2.872281323 Solving 1.5 + x = 2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 2.872281323 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 2.872281323 + -1.5 x = 2.872281323 + -1.5 Combine like terms: 2.872281323 + -1.5 = 1.372281323 x = 1.372281323 Simplifying x = 1.372281323Subproblem 2
x + 1.5 = -2.872281323 Simplifying x + 1.5 = -2.872281323 Reorder the terms: 1.5 + x = -2.872281323 Solving 1.5 + x = -2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -2.872281323 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -2.872281323 + -1.5 x = -2.872281323 + -1.5 Combine like terms: -2.872281323 + -1.5 = -4.372281323 x = -4.372281323 Simplifying x = -4.372281323Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.372281323, -4.372281323}Solution
x = {1.372281323, -4.372281323}
| 2.8x-43=1.3x+2 | | 5x-6=5x-1 | | X+19+x+19=x+29 | | -.15=.40+0.125p | | -9-4+2M=-9-7M+5 | | 24x^2+14x+108=0 | | 3*x^2=8-2x | | h(x)=x^4-4x+2 | | 4(3n-2)=(7n+4)+6 | | 45+3x+r=180 | | -.014x^2+.68x=0 | | 3x+23=52 | | 2(3x-1)+9=4x+15 | | A+bxc= | | 2x-3*2=x-9 | | 3x-124-12x=128 | | -4x+10=2y | | 2x-3+2x-3=x+9 | | 11x+19=41 | | 5x^6+x^4+5x^2+7x-65=0 | | -7k+3-6k=-35 | | 6x-4=7(x-8) | | y(2-y)=6-[y(y)+3y-4] | | 13=0.7x+2.50 | | x^2-120x=-2780 | | 3x+8y=-16 | | tanx=2.0417 | | 4(r+1.4)-6r=7.3 | | -5x-8y=59 | | 3a+b=5c | | 5x^2-7y^2=0 | | -4(-12+k)=-12 |